Implementation strategies for guidelines at ICUs: a systematic review. Issue 4 (8th May 2017) - Jordan, Portia; Mpasa, Ferestas; ten Ham-Baloyi, Wilma; Bowers, Candice
Abstract : Purpose: The purpose of this paper is to critically analyze empirical studies related to the implementation strategies for clinical practice guidelines (CPGs) in intensive care units (ICUs). Design/methodology/approach: A systematic review with a narrative synthesis adapted from Popay et al. 's method for a narrative synthesis was conducted. A search using CINAHL, Google Scholar, Academic search complete, Cochrane Register for Randomized Controlled Trials, MEDLINE via PUBMED and grey literature was conducted in 2014 and updated in 2016 (August). After reading the abstracts, titles and full-text articles, 11 ( n =11) research studies met the inclusion criteria. Findings: After critical appraisal, using the Joanna Briggs Critical Appraisal Tools, eight randomized controlled trials conducted in adult and neonatal ICUs using implementation strategies remained. Popay et al. 's method for narrative synthesis was adapted and used to analyze and synthesize the data and formulate concluding statements. Included studies found that multi-faceted strategies appear to be more effective than single strategies. Strategies mostly used were printed educational materials, information/ sessions, audit, feedback, use of champion leaders, educational outreach visits, and computer or internet usage. Practical training, monitoring visits and grand rounds were less used. Practical implications: Findings can be used by clinicians to implement the best combination of multi-faceted implementation strategies in the ICUs in order to enhance the optimal use of CPGs. Originality/value: No systematic review was previously done on the implementation strategies that should be used best for optimal CPG implementation in the ICU.